Marathon man (Paramount Pictures, 2002)
A likeable Columbia graduate student and marathon runner unwittingly gets trapped in a terrifying drama revolving around a murderous Nazi fugitive, Christian Szell. Szell administers torture with the instruments of a surgeon and the dispassionate ease of evil personified.